Arachnology in Finland. 2 - Koponen, Seppo (Memoranda Societatis pro Fauna et Flora Fennica, 2012)
Activity of Finnish arachnologists during the second half of the 20th century is presented. About thirty persons are dealt with, and a selection of their publications is given. Differences in research subjects between universities can be found: in Helsinki mainly ecology and faunistics, in Jyväskylä behaviour studies, in Oulu faunistics, and in Turku taxonomy and systematics as well as ecology and faunistics.